An ATCA processor for Level-1 trigger primitive generation and readout of the CMS barrel muon detectors. (14th February 2023) - Bestintzanos, I.; Adamidis, K.; Euaggelou, I.; Fernandez Bedoya, C.; Foudas, C.; Lymperakis, A.; Manthos, N.; Navarro, A.; Papadopoulos, I.; Redondo, I.; Sotiropoulos, S.; Sphicas, P.; et al.
Abstract: An ATCA processor was designed to instrument the first layer of the CMS Barrel Muon Trigger. The processor receives and processes DT and RPC data and produces muon track segments. Furthermore, it provides readout for the DT detector. The ATCA processor is based on a Xilinx XCVU13P FPGA, receives data via 10 Gbps optical links and transmits track segments via 25 Gbps optical links. The processor is instrumented with a Zynq Ultrascale+ SoM connected with an SSD which provides the necessary resources for enhanced monitoring and control information. The design of the board as well as results on its performance are presented.